Assessment of stress conditions for carotenoids accumulation in Chlamydomonas reinhardtii as added-value algal products - Samar A. El-Mekkawi; H. S. Hussein; S. A. Abo El-Enin; N. N. El-Ibiari (Bulletin of the National Research Centre, 2019)
Abstract Background Microalgae, the third-generation source of biofuel have invaluable bio-refineries such as carotenoids. The accumulation of carotenoids in the algal cell is based on several parameters during algal growth. Some of these parameters are irradiance and cultivation periods which figures the photoperiod during algal growth. In this work, 0.6 g/L Chlamydomonas reinhardtii, green algae strain, was cultivated using the BG-11 medium in bubble column photobioreactor illuminated by white cool fluorescent 24 h per day, irradiance range 40.5–149 μmol.m−2.s−1, and cultivation period range 10–20 days. The carotenoids were extracted using two solvents, petroleum ether, and ethyl acetate in ratio 7:3. The carotenoids fractions were quantified using HPLC and the design expert program 8.6 was used to optimize the irradiance and cultivation period in order to gain maximum carotenoids accumulation in C. reinhardtii using response surface method. Results The results revealed that the optimum conditions of C. reinhardtii cultivation are illuminating the culture 24 h a day for 10 days with irradiance 149 μmol.m−2.s−1 producing 0.85 mg/g astaxanthin, 0.87 mg/g lutein, and 0.64 mg/g β-carotene, as a maximum value of accumulating carotenoids in 2.15 g/L biomass yield. Conclusions High irradiance and cultivation period are two essential parameters for accumulating carotenoids in algae. Response surface method is an affordable method to optimize these parameters simultaneously via predicting a model describe the relation and analyze the results statistically. The experimental verification of results proved the model’s validity. The prospective research is going to study the effect of more parameters on carotenoids accumulation in algae.